THE REPRESENTATION OF RACISM IN TILL (2022) FILM BY CHINONYE CHUKWU - Ahmad, Noor Islamiyah; Ariani, Setya; Sanhadi Rahayu, Famala Eka (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
One of the social problems that often arise is racism. Racism is injustice against other races. Therefore, this study discusses the representation of racism in Till’s (2022) film by Chinonye Chukwu. This research aims to describe the levels of racism using Jones’ theory and the emotional impacts of racism using Rosenblat’s theory in Till’s film, which Mamie Till experiences as the main character. The researchers also used the qualitative method, sociological approach, and Mikos data analysis. In this study, the researchers found that Mamie Till experienced three levels of racism. The first institutionalized racism that Mamie experienced was differential access to services and opportunities. Second, personally mediated racism appears as a lack of respect, dehumanization, discrimination, prejudice, scapegoating, and acts of omission. Third, internalized racism in Mamie is resignation. The racism experienced by Mamie made her feel the emotional impacts of racism. The first is grief, in the form of emotional pain, affects the individual's functioning, and sadness. Next is rage, in the form of intense anger. The last humiliation, in the form of demeaned and discredited